Stay alive safety for journalists - Clavio, Arnold; Philippine center for Investigative Journalism ([Quezon City] Philippine Center for Integrative Journalism, 2006)
Philippines has been called one of the most dangerous places in the world for journalists. Fifty-six have been killed in the last two decades, and many other threatened for exposing wrongdoing committed by people in power. A video of practical tips that journalists can apply in dealing with threats to their lives and safety. Its message is that journalists need not and should not be sitting targets; they can and be should take steps to protect themselves and deter would-be assassins.
Summary from container.
Keywords: Journalists -- Safety measures. -- Philippines; Crime and the press -- Philippines; Political crimes and offenses -- Philippines